Particle swarm optimization based fuzzy logic MPPT inverter controller for grid connected wind turbine - Parvin K.; Kit Y.K.; Jern K.P.; Hoque M.M.; Hannan M.A. (International Journal of Renewable Energy Research, 2023)
Computer circuits; Controllers; Electric power system control; Electric power transmission networks; Energy conversion; Heuristic methods; Maximum power point trackers; Particle swarm optimization (PSO); Wind; Wind power; Wind turbines; Fuzzy logic control; Grid-connected; Hill climb search; Inverte; Maximum Power Point Tracking; Particle swarm; Particle swarm optimization; Swarm optimization; Wind energy conversion; Fuzzy logic